Adsorption Isotherm And Kinetic Models For Removal Of Methyl Orange And Remazol Brilliant Blue R By Coconut Shell Activated Carbon - Hee Tian Hii (Tecno Scientifica Publishing, 2021)
Adsorption technology is one of the efficient and facile method used for wastewater treatment. In this research, coconut shell, an agricultural solid waste was converted into activated carbon via furnace induced and zinc chloride chemical activation techniques. The activated carbon was prepared at activation temperature of 600°C. Anionic dyes, Methyl Orange (MO) and Remazol Brilliant Blue R (RBBR) have been selected due to their harmful effect to the environmental and human. Various effect of parameter such as initial dye concentration, initial pH, adsorbent dosage and agitation speed in batch system were investigated to obtain the optimum condition for both dye adsorption on activated carbon. The optimum dye removal efficiency was around 99% when 5g/L of activated carbon was used. Pseudo-second-order model was the best fitted model with highest correlation compared to other kinetic models. The adsorption behaviour of MO was perfectly presented by the Freundlich model while RBBR was well described by Langmuir model. The maximum adsorption capacity for MO was 59.17mg/g and RBBR was 35.09mg/g. Fourier-transform infrared spectroscopy (FTIR) was utilised to analyse the chemical characteristics of activated carbon before and after adsorption.